(untitled) (Research, Society and Development, 2019)
In order to provide acoustic comfort to the human being, over time, different materials and techniques have been developed for application in walls, partitions, ceilings and slabs. Some important materials found on the market are gypsum board, fiberglass, rock wool, EPS (Expanded Polystyrene). Considering the interference that the noise has caused in the buildings, in the present times, and thinking about contributing to the thematic, this work was sought the comparative study, through bibliographical and market research, among the main materials used for acoustic treatment.